Head Teacher's Job Satisfaction: At Community Schools in Dadeldhura District (Research Journal, 2023)
In the current situation, job satisfaction is one of the most important issues in organizational and leadership studies because it directly impacts individuals' sense of commitment to their job and belonging in the workplace. However, there is currently no general agreement in the educational research on job satisfaction and its definition. This was a quantitative approach with the survey research design method. For this, the questionnaire was used to collect data. There were 57 head teachers as the sample from the Dadeldhura district. A questionnaire was sent via e-mail to collect data, and collected data were analyzed using SPSS 25 version chi and phi as the test. About fifty and fifty percent of males and females are head teachers. Most of them were from the village area with Master’s degree qualifications. The p-value of males and females in salary satisfaction was found to be 0.14, which is not significant. Similarly, the p-value of age and professional satisfaction was 0.45 which is also not significant. Fifty percent of head teachers were males and females which is good. Likewise, 76.7% of the head teachers have Master’s great degree qualifications. More than 66% of the head teachers were satisfied with their co-workers working happily which can be interpreted as a good result in comparison to others. Most of the head teachers were from the village area of the Dadeldhura district. Females are also capable to get as higher a position as males that also reflected that the salary satisfaction level of males and females was not significant in terms of age and professional satisfaction.